Synthesis and characterization of polypyrrole doped with anionic spherical polyelectrolyte brushes - N. Su; H. B. Li; S. J. Yuan; S. P. Yi; E. Q. Yin (eXPRESS Polymer Letters, 2012)
The procedures for the synthesis of polypyrrole (PPy) doped with anionic spherical polyelectrolyte brushes (ASPB) (PPy/ASPB nanocomposite) by means of in situ chemical oxidative polymerization were presented. Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopic analysis suggested the bonding structure of PPy/ASPB nanocomposite. Scanning electron microscopy (SEM) was used to confirm the morphologies of samples. The crystallographic structure, chemical nature and thermal stability of conducting polymers were analyzed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Thermo-gravimetric analysis (TGA) respectively. Investigation of the electrical conductivity at room temperature showed that the electrical conductivity of PPy/ASPB nanocomposite was 20 S/cm, which was higher than that of PPy (3.6 S/cm).